Structured education using Dose Adjustment for Normal Eating (DAFNE) reduces long‐term HbA1c and HbA1c variability. Issue 6 (30th March 2018) - Walker, G. S.; Chen, J. Y.; Hopkinson, H.; Sainsbury, C. A. R.; Jones, G. C.
Abstract: Aims: Previous evidence has demonstrated that participation in the Dose Adjustment for Normal Eating (DAFNE) education programme can reduce HbA1c and severe hypoglycaemia in people with Type 1 diabetes. In a number of studies, increased HbA1c variability has been associated with higher diabetic morbidity and mortality. No studies have examined the impact of structured education on HbA1c variability in Type 1 diabetes. Methods: People with Type 1 diabetes who had attended DAFNE were identified for inclusion from the Scottish Care Information‐Diabetes dataset. HbA1c median and variability, expressed as coefficient of variation (CV) before and after DAFNE was calculated. Results: Some 1061 individuals participated in DAFNE education and 687 met the inclusion criteria. A significant median reduction in HbA1c [−3.5 mmol/mol (−0.3%)] was seen at 12 months with a significant reduction [−1.5 mmol/mol (−0.1%)] still seen at 60 months of follow‐up. HbA1c variability as measured by CV was significantly lower during the post‐DAFNE period: 0.08 (IQR 0.05–0.12) reduced to 0.07 (IQR 0.05–0.10); P = 0.002. Conclusion: The data confirm that DAFNE participation improves glycaemic control in Type 1 diabetes with benefits being sustained for 5 years. This study is the first to demonstrate reduced HbA1c variability after completion of structured education. This is new evidence of the beneficial impact of DAFNE on glycaemic profile. What's new?: HbA1c variability is known to be associated with mortality in people with Type 1 diabetes. Structured education (DAFNE) attendance is associated with a reduction in HbA1c variability. Reduced HbA1c variability following structured education may potentially be beneficial in people with Type 1 diabetes.